Rancang Bangun Floor Crane dengan Kapasitas Angkat Maksimum 1 Ton - Dandi Dwi Hamukti; Bayu Wiro Karuniawan; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
PT. Rekaindo Global Jasa is a company engaged in manufacturing and engineering consulting services and railway component support, most of the production is to support the trainproduction process of PT. INKA (Persero). PT. Rekaindo Global Jasa participates in producing electrical components such as Static Inverter (SIV), and Variable Voltage Variable Frequency (VVVF) Inverter. Electrical components such as transformers, batteries, and controllers contained in SIV and VVVF which weigh more than 100 kg, of course require tools for the lifting process to fit into the frame box of the SIV and VVVF. PT. Rekaindo Global Jasa uses forklifts to install these components, because the only lifting equipment available in the workshop is forklifts, hand pallets, and hoist cranes. The process of installing components using the lifting equipment is very inefficient and takes 1 hour to lift and install only 1 component. From these problems, the authors raised these problems as research material for the final project regarding the Design of Floor Crane with a Maximum Lifting Capacity of 1 ton. In this study using the Ulrich method with an output in the form of a floor crane that can lift objects easily and can be adjusted in height and arm length, so as to simplify and speed up componentassembly. Based on the results of the tests carried out, the floor crane was able to lift an object weighing 500 kg as high as 50 cm in 1 minute, 1 second, 8 seconds and by moving the object as far as 5 meters in 20 seconds, 40 seconds with 1 operator.